Impact of Husbands’ Healthcare Decision Making on Women’s Future Intention of Using Contraceptives in Bangladesh (Dhaka University Journal of Science, 2020)
The use of contraceptive is important for the reduction of maternal mortality, child mortality and to slow down the high population growth rate. The central objective of this study is to examine the association between husbands‟ involvement with healthcare decision making and women‟s future intention of using contraceptives. Bangladesh Demographic and Health Survey (BDHS), 2014 data is used for this purpose. To evaluate the association overall and stratified binary logistic regression models are employed as well as the odds ratios (OR) along with their 95% confidence intervals are specified. The adjusted effect of overall model shows that husband‟s involvement with healthcare decision making is significantly negatively associated (OR=0.82, 95% CI: 0.70, 0.95) with women‟s intention of using contraceptives. The adjusted effects of stratified models also demonstrate that the association is significantly negative among women in rural area, from middle income families, who are Muslim, having more than two living children, having current age 35 to 49, who are unemployed, whose husbands are 1 to 5 years older and secondary educated. These findings can help to address the men‟s role in family planning and to increase the current contraceptive prevalence rate in Bangladesh.Dhaka Univ. J. Sci. 68(2): 121-127, 2020 (July)